HUBUNGAN STATUS MEROKOK DENGAN KEJADIAN PENYAKIT PARKINSON - Willy Wijaya,* Thamrin Syamsudin,* Reggy Panggabean* (NEURONA, 2015)
INTRODUCTION PARKINSONS DISEASE PD IS THE SECOND MOST COMMON NEURODEGENERATIVE DISEASE WHICH CAUSES DISABILITY AND MAJOR ECONOMIC BURDEN THE INCIDENCE IS THOUGHT TO BE INCREASING WITH PROLONGED LIFE EXPECTANCY MEDICATION FOR PD HAS NOT BEEN SATISFYING NICOTINE IS THE NEW CANDIDATE FOR PD MEDICATION DUE TO ITS NEUROPROTECTIVE AND PRESYNAPTIC DOPAMINE RELEASE ENHANCEMENT EFFECT